Using data mining to understand how technology is expressed in curriculums to mediate learning outcomes - Wahl, Christian; Gade, Peter Nørkjær (Proceedings of the International Conference on Networked Learning, 2024)
The role of technology in education increases with the increasing need for students to master technology in their practice. However, mastering technology in modern practice has become increasingly complex and requires a deeper understanding of the technologies—technologies hold premises in terms of how they limit and enable actions. While correct use can improve practice, wrong use can harm and lay waste to resources and job satisfaction. Ensuring that students can manage this complexity requires that technology is actively reflected in realistic settings. However, how do the curriculums that steer education reflect the role of technology, and do the curriculums steer the learning of technology in an advantageous direction? In this study we investigate curriculums across educations to explore how technology is expressed. This exploration will be used to discuss the role of technology in education, how it is expressed in curriculums documents, and its potential advantages and problems. The exploration is done using text mining to identify and extract specific features of the natural language of the curriculums. The features extracted will be used to highlight specific patterns related to the use of technology in education. The contribution of this paper is twofold. Firstly, it provides a method for data mining to identify patterns of technological use in education, manifested in curriculums. Secondly, it shows how technology is viewed in education.